2021
DOI: 10.1002/adma.202101572
|View full text |Cite
|
Sign up to set email alerts
|

Precise Subcellular Organelle Targeting for Boosting Endogenous‐Stimuli‐Mediated Tumor Therapy

Abstract: to their noninvasive and specific treatment modality from selective irradiation. [1b] However, external energy, such as light, ionizing radiation or ultrasound, is required in these therapies, which obstructs their further development due to the limited penetration depth of the laser, safety concerns of radiation, therapeutic resistance and spatio-temporal constraints of some specific equipments. In-depth exploiting the differences between the tumor microenvironment (TME) and normal organs provides an altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 245 publications
0
38
0
Order By: Relevance
“…In the diseases in the TISIDB database, the expression of PCLAF was found to be positively correlated with activated CD4 T cells (Act CD4) and type 2 T helper (Th2) cells, suggesting that PCLAF may play a specific role in tumor immune infiltration. Mounting evidence has demonstrated that the tumor microenvironment (TME) plays a predominant role in the occurrence and development of tumors, which may accelerate the deterioration of tumors ( 62 , 63 ). Among the TISIDB database, in BRCA, Glioma, NSCLC, and UCEC, PCLAF was found to be highly expressed in CD8 T cells, regular CD4 T cells, CD8-poor T cells, monocytes or macrophages, and proliferating T cell fibroblasts, which suggests that PCLAF is closely related to tumor TME.…”
Section: Discussionmentioning
confidence: 99%
“…In the diseases in the TISIDB database, the expression of PCLAF was found to be positively correlated with activated CD4 T cells (Act CD4) and type 2 T helper (Th2) cells, suggesting that PCLAF may play a specific role in tumor immune infiltration. Mounting evidence has demonstrated that the tumor microenvironment (TME) plays a predominant role in the occurrence and development of tumors, which may accelerate the deterioration of tumors ( 62 , 63 ). Among the TISIDB database, in BRCA, Glioma, NSCLC, and UCEC, PCLAF was found to be highly expressed in CD8 T cells, regular CD4 T cells, CD8-poor T cells, monocytes or macrophages, and proliferating T cell fibroblasts, which suggests that PCLAF is closely related to tumor TME.…”
Section: Discussionmentioning
confidence: 99%
“…Hf-HI-4COOH achieved effective tumor-killing effects while avoiding damage to the skin and normal organs under low power density (0.3 W/cm 2 ) laser irradiation due to their high photothermal conversion efficiency and the intrinsic nucleus-targeting property. The tumor extracellular space is slightly acidic (pH = 6.5–6.8) because the tumor microenvironment is rich in lactate ( Zhen et al, 2021 ; Huang et al, 2022 ; Zhu et al, 2022 ). To further improve the targeting of cancer therapy, Phuong et al (2020) developed a slightly acidic environment-responsive carbon dot/TiO 2 nanocomposites for nucleus-targeting PTT.…”
Section: Passive Nucleus-targeting Nanodrugsmentioning
confidence: 99%
“…But the nucleus is not completely isolated from the cytoplasm for the nuclear pore complexes (NPCs) embedded in the nuclear membrane mediate material exchange and information transfer. NPC is a hydrophilic channel with a nuclear pore of ∼39 nm ( Zhen et al, 2021 ), through which hydrophilic small molecules can be diffused into the nucleus ( Zimmerli et al, 2021 ). However, most biomacromolecules are difficult to enter the nucleus via passive diffusion due to their large size.…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular targeting level, by conjugation of targeting moieties on the surface of nanoparticles, they could specifically target cancer cells with overexpressed receptors and increase cellular uptake and improve drug delivery efficiency [ 13 ]. For the subcellular level, researchers mainly focused on the organelle-targeted therapy that can further activate specific cellular pathways, enabling them to kill cancer cells [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%